2008
DOI: 10.1210/jc.2008-0783
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Elevates the Peak Overnight Production Rate of Acylated Ghrelin

Abstract: Acylated ghrelin has a multifold larger distribution volume and MCR than total ghrelin. An estrogenic milieu augments synthesis and/or acylation of ghrelin peptide without altering its MCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 47 publications
7
18
0
3
Order By: Relevance
“…Furthermore, estrogen reduces SST receptor expression, which in turn results in enhancing GH secretion [29][30][31]. Estrogen also enhances ghrelin-induced increase in GH secretion [18,32]. Therefore, estrogens play a major role in the regulation of GH secretion.…”
Section: Gh Secretion Regulation By Estrogensmentioning
confidence: 99%
“…Furthermore, estrogen reduces SST receptor expression, which in turn results in enhancing GH secretion [29][30][31]. Estrogen also enhances ghrelin-induced increase in GH secretion [18,32]. Therefore, estrogens play a major role in the regulation of GH secretion.…”
Section: Gh Secretion Regulation By Estrogensmentioning
confidence: 99%
“…Many studies reported that oestrogen up-regulates the ghrelin level. 96 However, oestrogen-replacement therapy in post-menopausal women increases serum total and acyl ghrelin secretion only to an insignificant extent, or even decreases serum total ghrelin level. 97 It was also found that plasma acyl ghrelin concentration, ghrelin expressing cells and ghrelin mRNA levels in the stomach increase transiently after ovariectomy in female rats.…”
Section: Oestrogenmentioning
confidence: 99%
“…98 In addition, ghrelin and oestrogen receptor immunoreactivities were demonstrated in the same cells, suggesting that oestrogen may have a direct effect on ghrelin expression. 96 …”
Section: Oestrogenmentioning
confidence: 99%
“…Another study reported suppressive effects of ovarian estradiol on stomach ghrelin gene expression as well as on the plasma ghrelin concentration (Matsubara et al, 2004). An additional recent study found that estradiol supplementation was followed by increased synthesis and/or acylation of the ghrelin peptide without any effect on its metabolic clearance rate in premenopausal women (Paulo et al, 2008), although another study did not confirm these data (Dafopoulos et al, 2010). Moreover, it has been reported that estrogen administration to a culture system of rat gastric tissue explants, induced a significant decrease in ghrelin secretion, but did not affect either mRNA or protein levels, and that testosterone treatment in orchidectomized rats did not affect gastric ghrelin secretion (Al-Massadi et al, 2010).…”
Section: Ghrelin and The Polycystic Ovary Syndromementioning
confidence: 99%